Analisis Kualitas Daya Listrik dan Keandalan Pelayanan pada Penyulang Nayak, Kaonak, Byak, Baliem, Napua, dan Interkoneksi 20 Kv PLN Wamena - Muhammad Yuski Firmansyah; Arief Marwanto (Jurnal Penelitian Rumpun Ilmu Teknik, 2025)
n the working area of ​​PT PLN (Persero) UP3 Wamena, the electricity distribution system still uses a radial configuration which has weaknesses in service continuity and feeder reliability on the 20 kV Medium Voltage Network (JTM). Geographical challenges and extreme climate in the Papua Mountains Province also exacerbate this condition. This study aims to analyze the reliability level of the Kaonak, Nayak, Baliem, Byak, Napua, and Interconnection Feeders using the SAIDI, SAIFI, CAIDI, and MAIFI index calculations according to the SPLN: 68-2 Year 1986 and IEEE 1366-2012 standards. The calculation results show that most feeders in 2023 and some in 2024 have not met the SAIDI and SAIFI standards according to SPLN and IEEE despite significant improvements in 2024. Meanwhile, the CAIDI index of all feeders is still within reasonable limits according to both standards. The MAIFI index cannot be calculated due to limited recloser equipment performance. Frequency quality still meets standards (50.2-50.3 Hz), but the total harmonic distortion (THD) of the feeders exceeds the limit with a value of ≥ 5%. The main network reliability issues are caused by difficult topography, limited access, and natural conditions that complicate disturbance management. Recommendations to improve network reliability include maintenance and optimization of primary distribution materials.